PENGEMBANGAN MODEL DIGITAL ECOSYSTEM BERBASIS APLIKASI FISHERMAN CARE UNTUK PENGUATAN KETAHANAN SOSIAL-EKONOMI KELUARGA NELAYAN PESISIR - Babussalam, A. Basuki; Hariri, Achmad; Wahyuni, Holy Ichda (LP2M Universitas Ibrahimy, 2025)
Fishermen families represent vulnerable coastal communities facing socio-economic instability due to fluctuating catches, long value chains, and limited literacy in social, economic, and legal risk management. This program addresses their multi-dimensional vulnerability through the development of a Digital Ecosystem Model based on the Fisherman Care application, designed as an integrated capacity-building platform. The intervention focuses on three aspects: (1) Family Education (Parenting) to strengthen digital communication and parenting skills; (2) Economic Empowerment, promoting product diversification and digital marketing for MSMEs; and (3) Legal Education, emphasizing fisheries regulations, business legality, and social protection. Using the Participatory Action Research (PAR) approach and quantitative evaluation through pre- and post-tests involving 60 participants from the Paciran Fishermen Community, the program recorded significant improvements across all areas. The economic aspect increased from 2.5 to 3.8, showing success in creating alternative family income sources; parenting literacy improved from 2.2 to 3.6, reflecting better digital parenting awareness; and legal understanding rose from 2.0 to 3.5, enhancing awareness of sustainability and business legality. These outcomes confirm that the integrated digital ecosystem model effectively strengthens fishermen families’ economic independence, family resilience, and legal literacy, supporting sustainable livelihoods in coastal communities.